Pelatihan Peningkatan Kapasitas dan Kualitas Pelaku Wisata di Sukabumi dalam Perspektif Komunikasi Pariwisata : Pengabdian - Heru Ryanto Budiana; Aat Ruchiat Nugraha; Lutfi Khoerunnisa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The tourist village in Sukabumi Regency possess significant tourism potential. However, the management of tourism destinations remains suboptimal. Additionally, the lack of skills and competencies among tourism actors presents a major constraint on the development of the region's tourism sector. This training program aims to enhance the capacity, quality, and roles of stakeholders in the tourism sector of Sukabumi Regency, particularly in relation to tourism communication. The training approach employed lectures, group discussions, and simulations (role playing), involving participants from tourism practitioners and enthusiasts across the tourist villages in Sukabumi Regency. The results of the training indicate an improvement in the abilities and skills of tourism actors in managing and effectively promoting tourism destinations.